Potential of Legumes: Nutritional Value, Bioactive Properties, Innovative Food Products, and Application of Eco-friendly Tools for Their Assessment. Issue 1 (2nd January 2023) - Carbas, Bruna; Machado, Nelson; Pathania, Shivani; Brites, Carla; Rosa, Eduardo AS; Barros, Ana IRNA
ABSTRACT: Legumes are an important and sustainable source of protein, dietary fiber and phytochemicals. Due to their composition, legumes have been used in enriched foodstuffs and recognized as a vital food resource for human diet, reducing the risk of cardiovascular disease and cancer. In the last years, in order to replace conventional analysis, more eco-friendly and faster methodologies have been applied to evaluate legumes' quality. The aim of this review is to encourage the consumption and production of legumes by promoting their dissemination, understanding their nutritional and functional value, and promoting the use of innovative methodologies to assess the composition of legumes.